Experimental study of cold-formed steel columns with openings - Mohd Aizat Herman, Mohd Rosdi (2019)
A series of column tests on C-section built-up steel has been conducted. The test specimens were firstly brake-pressed from high strength zinc-coated steel sheets and then two of the same members were connected back-to-back by self-drilling screws to form a built-up C-shaped section. The members had the nominal thicknesses of 1.2 and 2.0 mm. The column height of the specimens is 600 mm while the width is 103 mm. The column specimens were compressed between fixed ends where the steel plate is welded together between them. The purpose of the welded specimen is to hold the specimen to prevent them from falling apart and to obtained accurate result. The columns were failed by local, distortional, warping, flexural buckling and the interaction of these buckling modes is recorded. The failure modes and ultimate strengths of the column specimens were obtained. Most importantly the behaviour of the cold-formed steel is observed due to the different thickness and number of opening in specimens. As a result, the combination of two sections and thickness of specimen produce higher ultimate load. The result shows that thickness of 2.0 mm produces higher ultimate load than 1.2 mm. Position of holes also plays an important role in determining the ultimate load of specimen. From the experimental result, it shows that holes position that nearly to the support will decrease the ultimate load.